Estimation of the Public Debt Threshold of Malaysia - Kueh, Jerome; Venus, Khim-Sen Liew; Yong, Sze Wei (School of Social Sciences, USM, 2016)
Public debt becomes an essential global issue where a country has a tendency to seek alternative to borrow abroad in order to cushion any severe negative impact due to economic shocks. This is due to the assumption that a country can run into deficit in current year with the expectation that it will turn into surplus in the future. Malaysia as one of the emerging economies experienced decreasing trend of public debt of GDP in the 1990s, but in the 2000s, the scenario has changed and settled at 55% of GDP in 2015. This study adopts Threshold Regression method to determine the public debt threshold from 1991:Q1-2014:Q4 and to estimate the impact of the different debt levels on the economic growth in the long-run. There is a positive impact of debt on growth when public debt is below 41% of GDP and marginal impact when the debt level between 41%-53% of GDP. However, there is a detrimental impact on growth when public debt exceeds 53% of GDP. Therefore, policy developed should address in managing optimal level of public debt position and the quality of the debt.